(untitled) (Journal of Contemporary Philology, 2019)
This paper presents the results of the investigation of the English equivalents of the bi-construction used in pragmatic functions. The bi-construction in Macedonian is the main marker of the potential mood encoding hypotheticality and volition. Unlike English, which employs modal verbs to render these meanings, the bi-construction recruits both modal and lexical verbs in its structure. In non-conditional uses,potential mood forms may perform a range of pragmatic functions related to politenessand hedging. The goal of the investigation is to determine whether the pragmatic functiontends to be performed by bi-constructions based on modal or lexical verbsand whether this influences the choice of the translational equivalent in English. The results show that potential mood bi-constructions containing a modal verb are more frequent. The analysis confirmed the hypothesis that pragmatically used bi-constructions tend to be translated with the modal verb would. Moreover, there seems to exist a strongsemantic correlation between the bi-construction based on a particular modal verb and its English equivalent: thus saka chooses would, može–could, and treba–should.